Hybrid gamma camera imaging: translation from bench to bedside - Ng, Aik Hao (2018)
There is increasing interest in the use of small field of view (SFOV) portable gamma cameras in medical imaging. A novel hybrid optical-gamma camera (HGC) has been developed through a collaboration between the Universities of Leicester and Nottingham. This system offers high resolution gamma and optical imaging and shows potential for use at the patient bedside, or in the operating theatre. The aim of this thesis was to translate the HGC technology from in vitro laboratory studies to clinical use in human subjects.